Analysing the New Manifestations of External Debt in Developing Countries from 2000 to 2019 - Hanh, Vu Thi Kim (Modern Perspectives in Economics, Business and Management Vol. 5, 2021)
The debt rescheduling cases have significantly increased in recent years as well. The author employs an analytical qualitative and quantitative method to examine the new forms of external debt in developing nations from 2000 to 2019, and the findings are as follows: (1) Trends in external debt by country group, (2) External debt stocks of PPG long term debt, PNG long term debt increased between 2000 and 2019. (3) Between 2000 and 2019, the external debt stock as a percentage of GDP dropped, while PNG long and short term debt rose somewhat. ((4) In both 2018 and 2000, East and South-East Asia and Oceania and Latin America and the Caribbean exchanged first and second place in terms of largest amount, (5) Between 2000 and 2019, the highest amount of debt carried by SIDS was debt servicing on long-term external PPG. (6) In 2000 and 2021, the redemption schedules of both high-income and low- and middle-income countries increased the amount of redemption from around 2 to 2.32 trillion USD and 0.67 to 1.07 trillion USD, respectively. This demonstrates that they at least have a plan in place to resolve their external debt.